Tactical shapeshifting in business modeling - Walter van Andel (Journal of Business Models (JOBM), 2019)
This paper looks at "bottom-up" architecture firms. These firms focus on co-production and participation, as they develop designs that stimulate social change. As such, they are placed in a hybrid position between citizens and governments. The paper identifies four "business model tactics" they utilize in maneuvering between different institutional fields.
Keywords: 650; Business model tactics; institutional tensions; bottom-up architecture